Multimodal Texts of Political Print Advertisements in Ukraine - Batrynchuk, Zoriana; Yesypenko, Nadia; Bloshchynskyi, Ihor; Dubovyi, Kostiantyn; Voitiuk, Olena; Yesypenko, Nadia (SCIEDU Press, 2022)
Political print advertisements as an integral part of political propaganda contribute to creating a positive image of a politician or political party aiming to win popular votes. The effective combination of verbal and non-verbal (pictorial) components presupposes a purposeful influence on the electorate by means of activating existing socio-cultural schemas among voters. This study aims to analyze the generic structural potential of political print advertisements in Ukraine and to interpret the symbolic representation of the verbal and non-verbal levels of political advertisements. The data, encompassing 25 leaflets, was collected in 2020 during the local election campaign in Chernivtsi, Ukraine. The analysis has been conducted on two levels: literal and interpretative. Following the principles of Generic Structure Potential of advertisements (Cheong, 2004) we have outlined the GSP of print political advertisements in Ukraine. Thus, non-verbal (visual) components incorporate the lead (Locus of Attention (LoA) and Complement to the Locus of Attention (Comp.LoA) emblem, pictogram, verbal (linguistic) components involve Announcement (Opening), Enhancer, Slogan, and Call-and-visit Information. The next level of the analysis presupposed the interpretation of the obtained results. In accordance with this, the symbolic representation of the verbal level of political advertisements, incorporating patriotic, social, economic, and political slogans has been revealed. In terms of the symbolic representation of the non-verbal level of political advertisements, we observe the following in the analyzed material: the photo of the candidate, appearance, pictograms, and additional pictorial elements. The results indicate that the displays of the analyzed material are often congruent and explicit. Cases of incongruent and implicit displays have been observed as well. Such advertisements boost viewers‟ curiosity as they contain less verbal information. The results of the election show that the candidates whose advertisements incorporated symbolism and greater non-verbal information, led among the popular votes.
Keywords: multimodality; multimodal texts; political print advertisements; symbolism; graphic narration; generic structure potential